Analysis of the Sociodemographic and Psychological Factors of the Family Caregivers’ Self-Management Capabilities for Type 2 Diabetes Mellitus - Rondhianto Rondhianto; Nursalam Nursalam; Kusnanto Kusnanto; Soenarnatalina Melaniani; Ahsan Ahsan (Universitas Airlangga, 2019)
Introduction: The successful management of Type 2 diabetes mellitus is determined by the role of the family in self-management as a family caregiver. Many factors influence the capability of the family caregivers to carry out diabetes self-management. The purpose of this study was to analyze the factors that influence the family caregiver capability of performing diabetes self-management in people with Type 2 diabetes mellitus.Methods: The study design was an analytical observation using a cross-sectional approach. The sample was 220 family caregivers of people with Type 2 diabetes mellitus in Jember Regency, East Java Province, Indonesia. The multistage random sampling technique was used as the sampling technique. The research instrument was a questionnaire. The questionnaires used in this study were the Diabetes Management Self Efficacy Scale, the Spoken Knowledge in Low Literacy Patients with Diabetes Questionnaire, the Motives for Caregiving Scale, the Spirituality Index of Well-Being, the Sense of Coherence Scale, the Coping Scale, the Hensarling Diabetes Family Support Scale, and the Family Caregiver's Perception of the Role of the Nurse Questionnaire. The data analysis was performed using the Pearson correlation test, the Spearman rank test, and the multiple linear regression test.Results: The results of the Pearson correlation test and Spearman rank test showed that the sociodemographic factors associated with diabetes self management were age (p=0.000), gender (p=0.016), education (p=0.000), income (p=0.000), and kinship (p=0.000). The psychosocial factors associated with diabetes self management were diabetes knowledge (p=0.000), motivation (p=0.000), coping skills (p=0.000), spirituality (p=0.000), family coherence (p=0.000), family support (p=0.000) and the role of the nurses (p=0.000). The multiple linear regression test showed that the factors associated with diabetes self management were diabetes knowledge (β=0.047), motivation (β=0.094), coping (β=0.188), spirituality (β= -0.082), family coherence (β= −0.043), family support (β= 0.296) and the role of the nurses (β= 0.512).Conclusion: Efforts to increase the family caregiver’s capabilities in terms of diabetes self-management should pay attention to the socio-demographic and psychosocial factors to prevent complications and to improve the health status, and quality of life of people with Type 2 diabetes mellitus.